Fatigue life prediction of aero-engine compressor disk based on a new stress field intensity approach. (1st January 2020) - Zhao, Bingfeng; Xie, Liyang; Song, Jiaxin; Ren, Jungang; Wang, Bowen; Zhang, Shijian
Highlights: An improved stress field intensity approach is built for aero-engine compressor disk. Symmetrical line of notch is simplified as a fictitious cantilever beam structure. The new model is simplified to a multiple integral form on the symmetrical line. Effectiveness of the improved approach for compressor disk is verified by experiment. Abstract: In this paper, an improved stress field intensity approach is proposed for fatigue life prediction of compressor disk. The underlying physical mechanism of notched component is considered in the new model based on the fictitious cantilever beam structure, which is extremely important for both scientific research and industrial production. The influence of field radius on the solution of stress field intensity is fundamentally weakened in this new model, making the calculated field strength has an objective and accurate solution. In addition, on the basis of the simplification of stress distribution at the notch root of component, the form of the correction parameter calculation is transformed into a multiple integral form on the symmetrical line of notch root. Finally, in order to verify the effectiveness of the improved stress field intensity approach proposed in this paper, fatigue experiments were conducted to simulate the failure of the root transition of compressor disk mortise. Comparing results with the other two traditional approaches, it is evident that accuracy and stability of the improved stress field intensity approach are superior to that of the other two approaches. Graphical abstract: Image, graphical abstract